TINJAUAN YURIDIS EKSISTENSI HAKIM PENGAWAS DAN PENGAMAT DALAM SISTEM PERADILAN PIDANA INDONESIA - Maroni Maroni (Fiat Justisia: Jurnal Ilmu Hukum, 2007)
Monitoring and observation of court decisions made by judges is a new institution in the criminal procedural law in Indonesia. Through monitoring and observation of expected gaps (gap) between what the judge decided and reality implementation of the criminal in prison can be bridged. Judges will be brought closer to the prosecutors and corrections officials so that judges can follow the development of the state of the convict. Keywords: Judge, Supervisor and Observer, the Criminal Justice System